EFFECT OF BOTANICALS ON THE INCIDENCE OF COMPETITOR MOULDS AND BIOLOGICAL EFFICIENCY OF GREY OYSTER MUSHROOM (PLEUROTUS OSTREATUS) - M. K. BISWAS (The Bioscan, 2015)
The main obstacle for increased production of oyster mushroom(Pleurotus spp.) in West Bengal isthe frequent contamination of the mushroom growing beds with micro flora. An experiment was conducted with a view to develop a suitable management practice against the competitor moulds of P.ostreatus in an eco- friendly manner. Eight different botanicals were tested along with the most popular chemical treatment (carbendazim 75 ppm +formalin 500 ppm) against the competitor mould fungi in vitro and in vivo. Chemical treatment was found to be most effective in reducing the mycelial growth of five contaminants (65.4 to 86.6%) in vitro and checked the incidence of competitor moulds 81.36 % in vivo, which increased the yield of mushroom up to the tune of 35.20 % (106 % B.E.).A. indica (neem) showed its supremacy among all the botanicals tested and gave minimum effect on the growth of mushroom mycelium (4%) and exhibited maximum inhibitory effect (54.1 to 71.6 %)against Aspergillus spp., Trichoderma spp., Coprinus spp., and Penicillium spp. which was and found to be less effective against Sclerotium rolfsiiin vitro followed by extracts of Pongamia pinnata (6.7 %) and (42.4 to 61.3%) inhibition respectively against the mycelium of P. ostreatus and mould fungi. A range of 35.3 to 62.4% reduction in the incidence of inky caps (Coprinus sp.) and 26.3 to 68.4% reduction in green moulds(Trichoderma spp.) were recorded with different phyto-extracts. All the botanicals except Acacia nilotica reduced the incidence of competitor moulds (18.18 to 70.91%) in mushroom beds which resulted in an increaseof yield up to the level of 21.3 %. The information provides an alternative method of surface sterilization of substrates under the agro-ecological conditions of lateritic belt of West Bengal, India, which can minimize the use of fungicides in mushroom cultivation.